APLIKASI METODE FUZZY MADM TOPSIS DALAM MENGANALISIS KEPUASAN PELANGGAN TERHADAP KUALITAS PELAYANAN PERUSAHAAN DAERAH AIR MINUM TIRTANADI BELAWAN - Dernawati . Lubis; Abil . Mansyur (Universitas Negeri Medan, 2017)
Abstract: The quality and quantity of both ground and surface water in Belawan Area have deteriorated in the recent years. Despite of the loss, this could become opportunities for PDAM to get customers since there are not many choices left for the community. High economic growth allows the rising of community’s willingness to pay, especially for basic needs such as water. As a consequence of the increasing customers, PDAM has to maintain its services. Evaluation and customer satisfaction’s analysis are absolutely needed to be held regularly. Through this evaluation, PDAM will be able to arrange some strategies to maintain its existing customers and at the same time trying to draw more new customers. In this research, data analysis will employ Fuzzy MADM TOPSIS Method using structured questionnaire. The intended result of the study has a conclution that the customer satisfaction of the service quality PDAM Tirtanadi Belawan have gratified because the highest preference value that gratified alternative has 0.8194. From the 14th criteria of customer satisfaction that very gratifying is the courtesy, service security, that gratified is the service procedure, service conditions, clarity service, ability, justice, expense equity, expense certainty, environment freshmen, that enough gratify is discipline, responsibility, service speed, schedule certainty. The quality of service PDAM Tirtanadi Belawan is good.Keywords: Fuzzy MADM TOPSIS Method, Customer satisfaction, Service Quality.